PKPD Modeling of the Inoculum Effect of Acinetobacter baumannii on Polymyxin B in vivo - Chauzy, Alexia; Akrong, Grace; Aranzana-Climent, Vincent; Moreau, Jérémy; Prouvensier, Laure; Mirfendereski, Hélène; Buyck, Julien M; Couet, William; Marchand, Sandrine (Frontiers in Pharmacology, 2022)
The reduction in antimicrobial activity at high bacterial counts is a microbiological phenomenon known as the inoculum effect (IE). In a previous in vitro study, a significant IE was observed for polymyxin B (PMB) against a clinical isolate of Acinetobacter baumannii, and well described by a new pharmacokinetic-pharmacodynamic model. Few in vivo studies have investigated the impact of inoculum size on survival or antibiotic efficacy. Therefore, our objective was to confirm the influence of inoculum size of this A. baumannii clinical isolate on PMB in vivo effect over time. Pharmacokinetics and pharmacodynamics of PMB after a single subcutaneous administration (1, 15 and 40 mg/kg) were studied in a neutropenic murine thigh infection model. The impact of A. baumannii inoculum size (105, 106 and 107 CFU/thigh) on PMB efficacy was also evaluated. In vivo PMB PK was well described by a two-compartment model including saturable absorption from the subcutaneous injection site and linear elimination. The previous in vitro PD model was modified to adequately describe the decrease of PMB efficacy with increased inoculum size in infected mice. The IE was modeled as a decrease of 32% in the in vivo PMB bactericidal effect when the starting inoculum increases from 105 to 107 CFU/thigh. Although not as important as previously characterized in vitro an IE was confirmed in vivo.